Society In Early Medieval Kashmir: A Study Of Attire And Adornment (Journal of Namibian Studies : History Politics Culture, 2023)
The study aims to explore the social and cultural significance of attire and adornment in early medieval Kashmir. Attire and adornment were not just limited to aesthetics, but also reflected the cultural, social, and economic status of an individual. The study explores the material culture of both men and women during early medieval Kashmir, emphasising the differences in their dressing practices. The primary objective of the study is to investigate the role of attire and adornment in shaping the identity and social stratification of early medieval Kashmiri society. Further, it seeks to understand how clothing and ornamentation were used to denote gender, occupation, marital status, and religious affiliation. To achieve these objectives, the research draws on a multidisciplinary approach, utilising archaeological, anthropological, and historical sources. The findings of the study suggest that attire and adornment played a significant role in shaping the identity and social structure of early medieval Kashmiri society. Clothing and ornaments served as markers of status and identity, and were also used to signal the wearer’s religious and cultural affiliation.